Analysis Of Water Content and Soil Temperature ProfilesIn Cayenne Pepper (C. Frutescens L ) Cultivation Using Several Types Of Mulch - Kanikayani, Ni Made Dea; Sumiyati, Sumiyati; Bintang, Ida Ayu (Jurnal BETA (Biosistem dan Teknik Pertanian), 2026)
The purpose of this research is to water content and soil temperature profile content on mulch for cultivation of cayenne pepper plants with different types of mulch. This research use random design group, every each concist of five treatment and three repetation. Which is a treatment without mulch treatment, silver plastic mulch treatment, black plastic mulch treatment, clear plastic mulch treatment , and rice straw mulch treatment. The variable observed of soil temperature using a temperature sensor DS18B20 while for soil water content using the gravimetric method. Measurement of temperature and soil water content was carried out 3 times, namely at the 3 days, 30 days , and 60 days after planting . The result of the temperature and soil water content is made a profile of the temperature and soil water content in the mulch using the contour line method. The results of the soil temperature research show the profile contour when the at 3 days, without mulch distribution profile is 29-33 0C, silver plastic mulch 28-32 0C, black plastic mulch 29-34 0C, clear plastic mulch 28-32 0C and rice straw mulch 25-300C. At 30 days, without mulch distribution profile is 26-33 0C, silver plastic mulch 26-31 0C, black plastic mulch 27-33 0C, clear plastic mulch 28-32 0C and rice straw mulch 25-300C. At 60 days, without mulch distribution profile is 26-31 0C, silver plastic mulch 25-30 0C, black plastic mulch 27-32 0C, clear plastic mulch 31-37 0C and rice straw mulch 26-290C. The results of measurements of the soil temperature obtained in relation to the results of the soil water content